A Roadmap for the Molecular Farming of Viral Glycoprotein Vaccines: Engineering Glycosylation and Glycosylation-Directed Folding - Margolin, Emmanuel; Crispin, Max; Meyers, Ann; Chapman, Ros; Rybicki, Edward P. (Frontiers in Plant Science, 2020)
Immunization with recombinant glycoprotein-based vaccines is a promising approach to induce protective immunity against viruses. However, the complex biosynthetic maturation requirements of these glycoproteins typically necessitate their production in mammalian cells to support their folding and post-translational modification. Despite these clear advantages, the incumbent costs and infrastructure requirements with this approach can be prohibitive in developing countries, and the production scales and timelines may prove limiting when applying these production systems to the control of pandemic viral outbreaks. Plant molecular farming of viral glycoproteins has been suggested as a cheap and rapidly scalable alternative production system, with the potential to perform post-translational modifications that are comparable to mammalian cells. Consequently, plant-produced glycoprotein vaccines for seasonal and pandemic influenza have shown promise in clinical trials, and vaccine candidates against the newly emergent severe acute respiratory syndrome coronavirus-2 have entered into late stage preclinical and clinical testing. However, many other viral glycoproteins accumulate poorly in plants, and are not appropriately processed along the secretory pathway due to differences in the host cellular machinery. Furthermore, plant-derived glycoproteins often contain glycoforms that are antigenically distinct from those present on the native virus, and may also be under-glycosylated in some instances. Recent advances in the field have increased the complexity and yields of biologics that can be produced in plants, and have now enabled the expression of many viral glycoproteins which could not previously be produced in plant systems. In contrast to the empirical optimization that predominated during the early years of molecular farming, the next generation of plant-made products are being produced by developing rational, tailor-made approaches to support their production. This has involved the elimination of plant-specific glycoforms and the introduction into plants of elements of the biosynthetic machinery from different expression hosts. These approaches have resulted in the production of mammalian N-linked glycans and the formation of O-glycan moieties in planta. More recently, plant molecular engineering approaches have also been applied to improve the glycan occupancy of proteins which are not appropriately glycosylated, and to support the folding and processing of viral glycoproteins where the cellular machinery differs from the usual expression host of the protein. Here we highlight recent achievements and remaining challenges in glycoengineering and the engineering of glycosylation-directed folding pathways in plants, and discuss how these can be applied to produce recombinant viral glycoproteins vaccines.